Preliminary Interpretation of the magnetic anomalies of the Eastern Vietnam sea and adjacent region a - Minh, Lê Huy; Hùng, Lưu Việt (Vietnam Journal of Earth Sciences, 2018)
In this paper we showed that the reduction to the pole at low latitude based on a Wiener filtering approach of Hansen and Pawlowski could be applied on the magnetic equator if the magnetic boundaries are not paralel to magnetic meridians. Using this reduced-to-the-pole method, we have found that the geologic boundaries determined from the reduced-tothe-pole magnetic anomalies of the Eastern Vietnam sea and adjacent regions correlate remarkably well with the major geological features, including majorfaults, seafloor spreading segments, volcanic or intrusive blocks ... These results could be considered as very important informations to reconstruct the tectonic history of the region.